Aventuras de una negrita en busca de Dios - Shaw, Bernard, 1856-1950 (Serie Narrativa (Galaxia Gutenberg (Firm)), 2014)
Shaw caught a ton of grief for this 1932 novel. The protagonist is an African native girl recently converted to Christianity. She goes in search of God, literally walking into the bush to seek her maker. Instead, she finds numerous religious figures and philosophers, ranging from Noah to Voltaire.